The factors that influence career decision making among undergraduate: A case study in UiTM Kelantan / Muhammad Nasyran Ab Rahman - Ab Rahman, Muhammad Nasyran (Bachelor of Science (Hons) Statistics, 2014)
Students all over the world are faced with the problem regarding career decision making. Moreover, this phenomenon becomes more difficult when facing prospective undergraduate. This study was conducted to determine the relationship between financial benefits, non-financial benefit, interpersonal factors and intrinsic factors on career decision making. Target population selected from undergraduate students of Universiti Teknologi MARA Kelantan. Based on population size, 337 students are defined by using stratified sampling technique from four different faculties. Questionnaire was used as data collection and Structural Equation Modeling to analyze the inter-relationship between construct. Since the questions have the reliability and validity, an accurate data are required to proceed on several statistical techniques. As a result, financial benefits and intrinsic factor have significant effect on career decision making. While, non-financial benefits and interpersonal factors are not supported the hypothesis